Sistem Pakar Deteksi Penyakit THT Menggunakan Metode SAW - Samsir; Muhammad siddik; Azrai Sirait (CSRID (Computer Science Research and Its Development Journal), 2026)
Ear, Nose, and Throat (ENT) disorders are common health issues that require timely intervention from the early stages to prevent complications. However, a shortage of ENT specialists and the unequal distribution of healthcare services hinder optimal consultation and initial diagnosis, particularly in areas with limited access to healthcare. While various studies have developed disease diagnosis systems using inference methods—such as Forward Chaining and Certainty Factor—the application of the Simple Additive Weighting (SAW) method as a Multi-Criteria Decision Making (MCDM) approach to rank potential diseases based on symptom combinations remains relatively limited. This study aims to develop a web-based expert system for the initial diagnosis of ENT disorders by utilizing a knowledge base derived from ENT specialists and implementing the SAW method as a decision-making mechanism to identify the most likely disease (the alternative with the highest preference value). The knowledge base is represented through relationships between symptoms, diseases, symptom weights, and management guidelines. The diagnostic process involves constructing a decision matrix, normalizing values, weighting symptoms, and calculating preference values ​​using the SAW method. Developed using PHP and MySQL, the system provides initial diagnostic recommendations and management advice based on user-selected symptoms. This research contributes by applying the SAW method as a multi-criteria decision-making mechanism within an ENT diagnosis system, thereby making the process of identifying potential diseases more systematic, transparent, and adaptable to changes in the knowledge base